Ecotourism : transitioning to the 22nd century - Wearing, Stephen; Schweinsberg, Stephen (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Since the first edition of the title, ecotourism has become a major phenomenon in tourism and society in many countries and regions throughout the world. The profusion of experiences has generated a variety of means of theorizing, analysing and marketing ecotourism, all that have yet to be encompassed in one book. Ecotourism fills the gap by synthesising the changes in thinking and society over the last decade. This third edition has been fully revised and updated to include: updated chapters addressing modern thought and discourse, including neoliberalism, consumer culture and quality management in the ecotourism industry; critical analysis drawn from a range of theoretical frameworks, which models and advances the thinking in ecotourism towards a socio-geographical analysis; new and international case studies from emerging markets such as China and Brazil. Providing a critical introduction to the analysis of tourism from a sociological and geographical perspective, the title is essential reading for higher-level and graduate students and researchers in tourism, sociology and geography. It will also be of interest to environmental groups and practitioners.
OCLC-licensed vendor bibliographic record.
Keywords: Ecotourism; BUSINESS & ECONOMICS -- Industries -- Hospitality, Travel & Tourism; BUSINESS & ECONOMICS -- Management